Islamic Values in the Munggahan Tradition in Sundanese Society - Yunika Sari; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the Islamic values contained in the Munggahan tradition to welcome the holy month of Ramadan in Sundanese culture. The method used is a qualitative method of literature study and field study with a descriptive analysis of what is felt by the author in everyday life. The descriptive analysis technique is to produce complex and clear data. The research discussion includes the understanding of the Munggahan tradition, the Munggahan tradition according to Islamic law and the Islamic values contained in the Munggahan tradition of welcoming the holy month of Ramadan in Sundanese culture. This study concludes that the Munggahan tradition in Sundanese culture is an ancestral cultural heritage that is maintained by the Sundanese people to the present, as an effort to preserve Sundanese culture which is part of the cultural wealth in Indonesia, which has many benefits and contains Islamic religious values. In Islamic law, this uploading tradition is allowed. Although in Islamic law, the Munggahan tradition does not contain texts in the Qur'an, but the Munggahan tradition does not contradict, nor neglect the syar'i propositions, and the existence of this tradition is accepted especially in the Sundanese, and has a lot of wisdom and benefits. Apart from being a culture, the Munggahan tradition also has Islamic values, namely the values of faith, practice, worship, local wisdom and the value of ukhuwah Islamiyah. With the Munggahan tradition, it is hoped that it can maintain the treasures of Indonesian culture which also adheres to Islamic teachings.